Otimização de parâmetros de soldagem por resistência para redução de respingos em juntas soldadas na indústria automotiva - Vicente, Rômulo Borba (2018)
Resistance Welding is a process that allows a high productivity, does not use addition material and presents an excellent quality in welded joints. Due to its characteristics, it is widely used in the automobile industry. With the use of high performance steels and structural adhesives in the union of the plates, a greater challenge arises in the parameterization of the weld to guarantee the absence of expulsion (welding splash), maintaining the quality of the welded joint. This work aims for the characterization of brazed welds and to optimize the reduction of weld spatter, which affect the safety and quality of the process. On the first part is detailed the formation of welding nucleus, splashes and associated parameters such as: time, current, force, resistance and materials are presented. Since welding time is a variable that directly affects the productivity in the industry and the material is a project imposition, this work analyzes the variables current and energy to evaluate the limits of formation of the expulsions in welded joints without the use of structural adhesives and with their use. In order to evaluate the parameters, visual analysis and energy results of the process for the welded plates were used to determine a better configuration, keeping the process free of expulsions and guaranteeing the necessary mechanical resistance for welded joints. The results showed that there is a parameterization capable of reducing the amount of welding expulsion and that the structural adhesives influence directly the parameterization of the points in order to avoid the formation of welding splash.